Laptop desk design / Hanani Yuhaniz and Muhammad Najib @ Hakimi Moh Yusoff - Yuhaniz, Hanani; Moh Yusoff, Muhammad Najib @ Hakimi (2009)
This project was conducted by final semester students of Diploma in Wood Industry. The objective of this study is to solve problems faced by people who have limited space on their desk. With that, this laptop desk is multifunctional yet compact.